Substitution in Child Speech - Umayya Idrees Younis (PROSPECTIVE RESEARCHES, 2023)
This study investigates one of the phonological processes used by children which is substitution in the speech of a two year old child speaking Mosuli Arabic. It is used by children as other processes such as Metathesis, Consonant harmony and so on to simplify their speech. Substitution occurs in all consonantal features which are voicing, place of articulation, manner of articulation and tafxim. It occurs initially, medially and finally.